Nghiên cứu nhiễm sắc thể philadelphia trên bệnh nhân bạch cầu kinh dòng hạt - Thanh, Bùi Thị Thu; Thăng, Nguyễn Duy; Hạnh, Nguyễn Thị Hồng; Tránh, Nguyễn Văn; Cương, Ngô Tứ; Thành, Hồ; Sơn, Nguyễn Văn; Hiền, Nguyễn Thị Thu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.